Dutch occupational physicians and general practitioners wish to improve cooperation. Issue 10 (1st October 1999) - Buijs, P; van Amstel, R; van Dijk, F
Abstract : OBJECTIVES: To investigate cooperation between occupational physicians (OPs) and general practitioners (GPs). METHODS: Literature review; structured interviews; questionnaires sent to randomised samples of OPs (n = 232) and GPs (n = 243). RESULTS: Actual cooperation is poor. However, more than 80% of both groups responded that they want to improve their cooperation, aiming at better quality of care. Obstacles identified by OPs include insufficient knowledge among GPs about occupational health services (OHSs) (57%) and their patients' working conditions (52%). OPs also consider that GPs suspect them of serving employers more than employees (44%) and of verifying reasons of absence, with information from GPs (34%). Responses from GPs confirm these two suspicions (48%, response 58%), adding obstacles like commercialisation of OHS, lack of financial incentives, etc. Both groups are unanimous about prerequisites for improvement, especially guaranteeing the professional autonomy of OPs (OPs 86%, GPs 76%). CONCLUSION: As a first step to overcome obstacles to cooperation, OPs must clarify their position to GP colleagues. Initiatives have been taken after presenting this study.